Treatise/architecture in Wang Shu’s work: three readings on fictionalizing cities and the Xiangshan Campus of the China Academy of Art - Xin, Jin (2018)
This work intends to investigate the relation between the architectural treatise and architecture through three case studies. In Vitruvius’s tradition, the treatise is taken as the ‘reasoning’ on the ‘making’. Nevertheless, from the semiotic point of view, the treatise and architecture, or more fundamentally, writing and building are different symbol systems. Both the mediums possess the making aspects. And they are in a concept-substance process also of formal analogy. This duality is demonstrated in the case studies on the Chinese architect Wang Shu’s PhD thesis Fictionalizing Cities and his built work the Xiangshan Campus of the China Academy of Art. Adopting a kind of semiotic approach, this study shows that Fictionalizing Cities and the CAA Campus are isomorphic forms. More generally speaking, the treatise and architecture are associated with two dimensions: they are developmental in time as well as transformational in space. Moreover, this formalist study distinguishes the treatise’s writing form and its social use. The latter is confined to the internal law of the former. The signification law permits one to distinguish the critique of culture and that of form in architecture. And the metaphor/metonymy contrast can describe the rhetoric nature of architectural critique discourses.